Financial frictions, international capital flows and welfare - Filippo Taddei (European Central Bank (ECB), 2018)
The connection between the financial crisis and global imbalances is controversial. This paper argues that this relationship is likely to be connected to the existence of heterogenous financial frictions in different domestic credit markets. By developing a general equilibrium model where adverse selection and limited pledgeability coexist, this work highlights why adverse selection may play a pivotal role in determining the different (often opposing) welfare effects of international capital flows on originating and destination countries. This perspective also advances an analytical framework that is flexible enough to analyze the global effects on investment allocation of the "Saving Glut", of the policies facilitating financial integration and macro-prudential policy.
Keywords: D53; E2; F3; 330; Limited Pledgeability; Asymmetric Information; International Capital Flows; Welfare; macro-prudential policy